Reliability, factorial validity, and interrelationships of five commonly used change of direction speed tests - Stewart, P. F.; Turner, A. N.; Miller, S. C. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Change of direction speed (CODS) is often considered a main determinant of successful performance in many team sports and is routinely measured using field-based tests. However, controversy regarding test selection still exists based upon the reliability and specificity of the tests. The purpose of this study was to determine and compare the reliability, factorial validity, and interrelationships of five frequently used CODS tests (Illinois, L-Run, Pro-Agility, T-test, and 505). Forty-four physical education students (male n = 24; female n = 20; age; 16.7 ± 0.6), who compete within team sports, to varying levels of competition, participated in this study. Three trials for each of the five tests were recorded. All tests had high (intraclass correlation coefficient) test-retest reliability (r = 0.88-0.95) and low typical percentage error (1.95-2.40%). The principle component factor analysis resulted in the extraction of one significant component which explained 89.52% of the total variance. All selected tests were positively and strongly correlated (r = 0.84-0.89). Based upon the results of this study, it was concluded that all tests are highly reliable and valid measures of CODS, with all tests assessing a general athletic ability to change direction. Future research should investigate the factorial validity of the CODS test within homogenous samples.